1982
DOI: 10.1530/acta.0.0990101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin on wound healing in diabetic mice

Abstract: In the present study wound healing was examined in normal C57B1/6 male mice, diabetic mice, non-treated; and in diabetic mice treated with insulin.Small dermal wounds were made in the ears of the mice 40 h after the initial injection of insulin or vehicle alone. All animals were biopsied 8 h later. The wounds were examined by light and electron microscopy and wound components (capillaries, fibroblasts, PMN's, oedema, collagen) were quantitated by lineal point analysis. The non-treated, diabetic mice demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Our results, with diabetic patients randomized to receive topical insulin or placebo in a prospective, double-blind and placebo-controlled clinical trial, show that the application of a cream containing insulin is able to significantly improve wound healing in these patients and, although the patients had very different sizes of ulcers, we observed complete healing at week 15 in all the 22 patients that used this cream. Previous pilot studies in animals or humans have employed topical insulin to accelerate wound healing in diabetes and, although these studies were not well designed, they all show an effect of insulin on this process [7], [8], [9], [10], [11], [12], [13], [14], [15], [55]. The insulin cream we made allowed us to prepare a homogenous cream, and improved the adherence of the cream to the surface of the wound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results, with diabetic patients randomized to receive topical insulin or placebo in a prospective, double-blind and placebo-controlled clinical trial, show that the application of a cream containing insulin is able to significantly improve wound healing in these patients and, although the patients had very different sizes of ulcers, we observed complete healing at week 15 in all the 22 patients that used this cream. Previous pilot studies in animals or humans have employed topical insulin to accelerate wound healing in diabetes and, although these studies were not well designed, they all show an effect of insulin on this process [7], [8], [9], [10], [11], [12], [13], [14], [15], [55]. The insulin cream we made allowed us to prepare a homogenous cream, and improved the adherence of the cream to the surface of the wound.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data, although not well controlled, showed that topical insulin accelerates wound healing in the skin of diabetic rats and humans [7], [8], [9], [10], [11], [12], [13], [14], [15], but in these studies no mechanism for this insulin effect was proposed or investigated. It is known that insulin stimulates the growth and development of different cell types, and affects proliferation, migration, and secretion by keratinocytes, endothelial cells, and fibroblasts [12], [16], [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies [42-44] found that insulin treatment by topical application or by injection accelerated wound healing. By contrast, Weringer et al [45] revealed that there was no detectable difference in the duration of the healing response in either insulin-treated or non-treated diabetic mice.…”
Section: Resultsmentioning
confidence: 91%
“…Since most uncomplicated wounds in normal skin of healthy people heal without significant problems, models of impaired healing were developed to mimic clinical conditions that impair healing in patients. Wound healing models involving the administration of chemotherapy, 2–7 radiotherapy, 8–13 infection of wounds, 14 malnutrition of animals, 15 the creation of a diabetic state, 16–18 and ischemia 19 have been created to study impairment of normal wound healing. Radiation‐impaired wound healing models have the advantage of being able to treat skin locally, without exerting a systemic effect on the treated animal.…”
mentioning
confidence: 99%